The reimplantation valve-sparing aortic root replacement technique for patients with Marfan syndrome: a single-center experience - Kremer, Jamila; Farag, Mina; Zaradzki, Marcin; Szabó, Gábor; Ruhparwar, Arjang; Kallenbach, Klaus; Karck, Matthias; Arif, Rawa (Scientific reports, 2019)
Valve-sparing aortic root replacement (VSARR) through reimplantation technique is widely regarded as optimal surgical approach for Marfan syndrome (MFS) patients. Perioperative and long-term data from all MFS patients undergoing VSARR using David’s technique at our center from 2007-2018 were analyzed. We included 56 patients with a mean age of 32.3 ± 12.3 years. Logistic EuroSCORE was 7.96 ± 5.2. Among others concomitant surgical procedures included aortic arch surgery (8.9%), mitral valve repair (23.2%) and replacement (1.7%). There were no operative deaths, nor in-hospital-mortality. One patient underwent re-exploration for bleeding, dialysis and pacemaker implantation was required in one case each. There was no occurrence of low-output syndrome nor neurological complications. Significant gender differences were not found, except for intraoperative blood transfusion occurring significantly more often in the female gender (p = 0.009). Despite significantly longer procedural times, concomitant surgery did not negatively impact overall outcome. Freedom of reoperation of the aortic root was 100% at 1 year, 97.7% at 8 years. Until last follow-up (61 ± 38 month) all patients survived, with no evidence of endocarditis. We emphasize once more that VSARR using David’s procedure is a safe method for MFS patients with excellent long-term results even if concomitant procedures are performed.